Coping with the COVID-19 pandemic: Strategies for controlling nosocomial infections in the observation area in a general hospital in China - Feng-Li Gao; Shu Ding; Juan Cai (Wolters Kluwer Medknow Publications, 2020)
This study shared experiences in implementing infection prevention and control strategies in an observation area to minimize nosocomial infections of COVID-19 in a 3A-level general hospital in China, including area division, human resources and teamwork, instructions for infection control, and the establishment of workflow management groups in the operation center. These experiences will be helpful to countries, especially developing countries, who are fighting against COVID-19 now and other infectious diseases in the future to control nosocomial infections.